DUCK (Anas platyrhincos Borneo) CULTIVATION IN HULU SUNGAI UTARA SOUTH KALIMANTAN (OVERVIEW OF MARKET, HUMAN RESOURCES AND FINANCING) - Muhammad Riza Firdaus; Ade Adriani; A. Yunani; Akhid Yulianto; Antonius G.S; Syahrituah S (Universitas Lambung Mangkurat, 2013)
Given Alabio ducks ( Anas platyrinchos Borneo ) is a commodity that can be developed on wetlands , the study aims to illustrate the potential and development of duck farms that can be relied upon by the provincial government in making policies for the advancement of this duck commodities , especially in the aspect of markets , human resources , and financial aspects . These three aspects have been given the results of several previous studies that the three aspects mentioned this is still an issue in the development of duck and production results . Hulu Sungai Utara as duck production centers serve as a test site . Qualitative analysis of the domain and toksonomi method used as a tool in analyzing the data of this study . The results show : First , aspects of financing shows that the business is viable and profitable , especially on a large scale . Second , the market requires a lot of innovation in creating related products. Third , explain aspects of human resource regeneration is still a problem and also the managerial constraints such as planning , standardization and quality in all phases .